2001
DOI: 10.1161/01.hyp.38.3.439
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Valsartan on Mechanical Properties of the Carotid Artery in Spontaneously Hypertensive Rats Under High-Salt Diet

Abstract: Abstract-The aim of this investigation was to evaluate the influence of a high-salt diet (HSD) on the effects of valsartan, an angiotensin II type 1 (AT 1 ) receptor antagonist, on carotid arterial stiffness and structure in spontaneous hypertensive rats (SHR). Carotid arterial stiffness was studied in SHR receiving a HSD or a normal-salt diet (NSD) from the 10th to 20th week of age. Within each of the 2 groups, the animals received treatment with either placebo or valsartan (30 mg · kg Ϫ1 · d Ϫ1 ) administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 42 publications
4
41
0
3
Order By: Relevance
“…The arterial stiffening associated with high dietary salt intake was not prevented by RAS blockade, thereby confirming a previous report (22) on the vascular effects of valsartan. These findings support the concept that dietary salt excess participates in the pathogenesis of reduced arterial distensibility and suggest that different mechanisms may operate in mediating the adverse effects of salt excess on conduit as well as resistance vessels.…”
Section: Discussionsupporting
confidence: 90%
“…The arterial stiffening associated with high dietary salt intake was not prevented by RAS blockade, thereby confirming a previous report (22) on the vascular effects of valsartan. These findings support the concept that dietary salt excess participates in the pathogenesis of reduced arterial distensibility and suggest that different mechanisms may operate in mediating the adverse effects of salt excess on conduit as well as resistance vessels.…”
Section: Discussionsupporting
confidence: 90%
“…We have previously shown that SHR receiving a sodium loading developed a higher level of wall stress with no upward shift of the Einc-wall stress curve. 14 In addition, administration of a high-salt diet alone for 4 weeks in uninephrectomized SD rats did not produced any significant increase in wall stress nor Einc (unpublished data). These findings indicate that in both normotensive rats and SHR, a high-salt diet does not modify the mechanical behavior of the arterial wall.…”
Section: Arterial Stiffnessmentioning
confidence: 90%
“…Previous reports have shown that high level of mechanical stress, 15,16 stimulation of the renin angiotensin system, 17,18 as well as high sodium intake 14,19 may stimulate Fn synthesis. Because in these studies the level of wall stress was high, it is difficult to distinguish its role from that of sodium or renin angiotensin system.…”
Section: Arterial Wall Hypertrophy and Compositionmentioning
confidence: 96%
“…39 In vivo arguments supporting cause-and-effect relationships between integrins and Fn and their impact on arterial stiffness were also obtained from studies on spontaneously hypertensive rats fed different levels of dietary sodium. 38 On a normal-sodium diet, AngII inhibition reduced mean BP, aortic Fn, and ␣ 5 ␤ 1 integrin, together with increased isobaric vascular distensibility. Under AngII blockade and a high-salt diet, mean BP was lowered significantly, but arterial distensibility and aortic Fn remained elevated and unmodified during the experiment.…”
Section: Cellular and Molecular Mechanismsmentioning
confidence: 98%
“…1 ECM attachment molecules interact with VSM cells, VSM cells and glycosaminoglycans, or various collagen fibers (collagen cross-links). 1,37 Because integrins transmit insideout and outside-in signals capable of modulating changes of vascular responses, Lacolley and colleagues [37][38][39] showed that adhesion molecules such as fibronectin (Fn) and its ␣ 5 ␤ 1 integrin receptor may contribute greatly to this modulation of wall stiffness. Results of studies conducted on young and old spontaneously hypertensive rats, and using aortic Fn and integrin immunolabel, suggested that more attachment sites between VSM cells and the ECM might be responsible for enhanced arterial rigidity.…”
Section: Cellular and Molecular Mechanismsmentioning
confidence: 99%